Proteomic Analysis of Excretory-Secretory Products of Mesocestoides corti Metacestodes Reveals Potential Suppressors of Dendritic Cell Functions. - Emilia Vendelova; Jeferson Camargo de Lima; Karina Rodrigues Lorenzatto; Karina Mariante Monteiro; Thomas Mueller; Jyotishman Veepaschit; Clemens Grimm; Klaus Brehm; Gabriela Hrčková; Manfred B Lutz; Henrique B Ferreira; Justin Komguep Nono (Public Library of Science (PLoS), 2016)
Accumulating evidences have assigned a central role to parasite-derived proteins in immunomodulation. Here, we report on the proteomic identification and characterization of immunomodulatory excretory-secretory (ES) products from the metacestode larva (tetrathyridium) of the tapeworm Mesocestoides corti (syn. M. vogae). We demonstrate that ES products but not larval homogenates inhibit the stimuli-driven release of the pro-inflammatory, Th1-inducing cytokine IL-12p70 by murine bone marrow-derived dendritic cells (BMDCs). Within the ES fraction, we biochemically narrowed down the immunosuppressive activity to glycoproteins since active components were lipid-free, but sensitive to heat- and carbohydrate-treatment. Finally, using bioassay-guided chromatographic analyses assisted by comparative proteomics of active and inactive fractions of the ES products, we defined a comprehensive list of candidate proteins released by M. corti tetrathyridia as potential suppressors of DC functions. Our study provides a comprehensive library of somatic and ES products and highlight some candidate parasite factors that might drive the subversion of DC functions to facilitate the persistence of M. corti tetrathyridia in their hosts.